Analytical Study of Ablution Spaces: Case Analysis of Mosques in Lahore, Pakistan - Malik, Ilyas; Jamil, Farah; Mujahid, Beenish (Annals of Human and Social Sciences, 2023)
The activity of performing ablution being a prerequisite for praying and reciting holy Quran has made ablution area an essential element of Mosque design. Its design has varied with the development of technology, new materials, cultural changes and wisdom of the designers or constructors and limitations of construction budget. Therefore, we find a variety of systems for ablution units in every mosque and prayer area during different times in different localities. The objective of research was to find most acceptable space dimension and design for the user’s comfort while performing this activity. Survey of three selected mosques in Lahore showed that none of the systems was perfect by all means and in each case nature of problems and level of satisfaction varied at the end of users. On the basis of user’s comments and physical observations, an analysis was carried out in terms of sizes and space dimensions of the ablution units designed by different architects in the three mosques of Lahore. Provision of different allied facilities that contribute to the satisfaction of users have also been studied. The results shows that the physical dimension of different elements of ablution units and user’s level of satisfaction in all three mosques are same in some of the elements. The study provides a preliminary design guidelines for design of ablution unit in mosques. The effort is supposed to benefit the architects and student of architecture in designing ablution units for the mosques. In addition to that recommendations can be incorporated in local building byelaws concerning the mosque and prayer area design.